Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The clinical peculiarities and differential diagnosis of Rett syndrome are reviewed from the Department of Pediatrics Children's Clinics, East Hospital, Goteborg, Sweden.